INOVASI STRATEGI EVALUASI SUMBER DAYA MANUSIA UNTUK PENINGKATAN PRODUKTIVITAS APARATUR DISHUB KOTA BANJARMASIN - Mia Della; Zakky Zamrudi; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The purpose of this study is to examine the most effective form of Human Resource Management (HRM) evaluation strategy innovation and analyze its impact on apparatus productivity improvement at the Banjarmasin City Transportation Agency (Dishub). The study employed a qualitative method with a case study approach. Data was collected through in-depth interviews with the Head of Agency, Head of HRM Management Division, and Apparatus Implementers, and analyzed using an interactive model.The results indicate that the most effective form of evaluation innovation is a Hybrid and Continuous Development-Oriented Evaluation System. This innovation is based on three pillars: (1) Strategic Integration (linking assessment to innovative project contributions and using simple 360-degree feedback), (2) Development Focus (transforming feedback into coaching sessions based on agile individual KPIs), and (3) Fairness and Motivation (utilizing frequent non-financial rewards and self-assessment mechanisms).The implementation of this innovation significantly improves apparatus productivity. The productivity increase is achieved through enhanced strategic focus and alignment (shifting from routine output to service outcome), improved technical competence via a fast learning culture, and increased internal motivation and work morale resulting from fair and prompt recognition. Overall, the HRM evaluation innovation serves as a catalyst for realizing a High-Performance Culture within Dishub Kota Banjarmasin..